2021
DOI: 10.1021/acs.jmedchem.1c00603
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, In Vitro and In Vivo Characterization of Selective NKCC1 Inhibitors for the Treatment of Core Symptoms in Down Syndrome

Abstract: Intracellular chloride concentration [Cl – ] i is defective in several neurological disorders. In neurons, [Cl – ] i is mainly regulated by the action of the Na + –K + –Cl – importer NKCC1 and the K + –Cl – exporter KCC2. Recently, we have reported the discovery of ARN23746 as the lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…Inhibition of NKCC1 by bumetanide and other loop diuretics is a double-edged sword in clinical medicine. On the one hand, antagonizing neuronal NKCC1 represents an emerging attractive strategy for the treatment of a wide range of brain disorders such as seizure and autism 14 , 53 , 54 . On the other hand, inhibition of NKCC1 also causes side effect of ototoxicity in the treatment of edema/hypertension 8 , 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of NKCC1 by bumetanide and other loop diuretics is a double-edged sword in clinical medicine. On the one hand, antagonizing neuronal NKCC1 represents an emerging attractive strategy for the treatment of a wide range of brain disorders such as seizure and autism 14 , 53 , 54 . On the other hand, inhibition of NKCC1 also causes side effect of ototoxicity in the treatment of edema/hypertension 8 , 9 .…”
Section: Discussionmentioning
confidence: 99%
“…DYRK1) have been recently identified, and certain pharmacological agents (e.g. a pharmacological inhibitor of the Na + -K + -Cl-importer) appears to show efficacy both in autism and DS models [ [59] , [60] , [61] , [62] ]. Further work is required to explore the potential connection of DS and autism and the potential involvement of various H 2 S-associated pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above study that demonstrated the beneficial effects of NKCC1-specific inhibitor bumetanide, commonly used clinically as a diuretic, it has been shown to be a useful treatment in mouse models of SZ , Down Syndrome (DS) (Deidda et al, 2015), Rett Syndrome (Banerjee et al, 2016), 22q11.2 deletion (DiGeorge) syndrome (Amin et al, 2017), neonatal epilepsy (Dzhala et al, 2005), and ID (Maset et al, 2021). More recent studies have further identified a novel therapeutic molecule known as ARN23746 (Savardi et al, 2020;Borgogno et al, 2021) and a series of KCC2 expression-enhancing compounds (KEECs) to be effective against the core symptoms exhibited by DS and ASD mouse models (Tang et al, 2019). Whereas ARN23746 targets NKCC1 selectively (thus limiting off-target diuretic side effects exhibited by bumetanide), the KEECs act via distinct cell signaling pathways [activation of the sirtuin 1 (SIRT1) or transient receptor potential cation channel subfamily V member 1 (TRPV1) pathways, or inhibition of fms-like tyrosine kinase 3 (FLT3) or glycogen synthase kinase 3β (GSK3β) pathways] to upregulate KCC2 expression at both mRNA and protein levels.…”
Section: Genetic and Pharmacologic Approaches To Modulate Kcc2 And Nk...mentioning
confidence: 95%